2019
DOI: 10.3343/alm.2019.39.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Microarray Analysis as a First-Tier Clinical Diagnostic Test in Patients With Developmental Delay/Intellectual Disability, Autism Spectrum Disorders, and Multiple Congenital Anomalies: A Prospective Multicenter Study in Korea

Abstract: Background To validate the clinical application of chromosomal microarray analysis (CMA) as a first-tier clinical diagnostic test and to determine the impact of CMA results on patient clinical management, we conducted a multicenter prospective study in Korean patients diagnosed as having developmental delay/intellectual disability (DD/ID), autism spectrum disorders (ASD), and multiple congenital anomalies (MCA). Methods We performed both CMA and G-banding cytogenetics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 30 publications
(52 reference statements)
2
44
1
3
Order By: Relevance
“…2,3 More recent studies on cohorts of patients with CA/ DD/ID have documented diagnostic yields ranging from 16% to 28%. [4][5][6] As a result, CMA is a well-established tool in clinical practice, yet this testing will not capture singlenucleotide variations (SNVs) or small insertion/deletions (indels), smaller structural variants, and other pathogenic variant types contributing to CA/DD/ID.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 More recent studies on cohorts of patients with CA/ DD/ID have documented diagnostic yields ranging from 16% to 28%. [4][5][6] As a result, CMA is a well-established tool in clinical practice, yet this testing will not capture singlenucleotide variations (SNVs) or small insertion/deletions (indels), smaller structural variants, and other pathogenic variant types contributing to CA/DD/ID.…”
Section: Introductionmentioning
confidence: 99%
“…SNP array can detect not only CNVs, but also uniparental disomy and chimera. CMA has the advantage of high throughput and high resolution, and has been proven to be a powerful diagnostic tool in cases with developmental delays/mental retardation, autism syndrome, multiple birth defects, etc 2 – 4 . With the wide application of CMA as a prenatal diagnostic technique, clinical values of chromosomal microdeletions and microduplications are increasingly recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous WES studies revealed a diagnosis rate of ∼25-30% in nonselective patients (Yang et al, 2013(Yang et al, , 2014Lee et al, 2014;Daoud et al, 2016;Retterer et al, 2016). Moreover, additional pathogenic and likely pathogenic CNVs were also identified in over 10% of patients (Sanmann et al, 2015;Homma et al, 2018;Jang et al, 2019). The development of NGS data based CNV calling algorithm makes it possible to identify SNVs and CNVs at same time.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, multiple researches on clinical utility and cost of WES have provided evidence endorsing it as a first-tier test for children with suspected monogenic disorders (Nguyen and Charlebois, 2015;Monroe et al, 2016;Stark et al, 2016;Hu et al, 2018). CMA has been used as a first-tier clinical diagnostic test in patients with developmental delay (DD)/intellectual disability (ID), autism spectrum disorders (ASD), and multiple congenital anomalies (MCA) since 2010 (Manning et al, 2010;Miller et al, 2010); and copy number variants (CNVs) detected by CMA explained the pathogenesis for over 10% of these cases (Sanmann et al, 2015;Homma et al, 2018;Jang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%